(untitled) (The Review of Diabetic Studies, 2021)
OBJECTIVE: Type 2 diabetes (T2D) is a multifactorial disease. Its occurrence and prognosis are affected by many genes, including KCNJ11, UCP2, and MTHFR. The objective of this study was to investigate the distribution of various variants of these genes and evaluate their contribution to the outcome of T2D. METHODS: 80 females with T2D and class I-II obesity in the age of 40-65 years old underwent a genetic study, a biochemical blood test, and indirect calorimetry. RESULTS: Carriers of C/T and T/T genotypes of the MTHFR gene had higher levels of cholesterol and triglycerides and lower levels of vitamin B6 and folate. The T/T genotype of the UCP2 gene was associated with higher levels of glycated hemoglobin, pre- and postprandial glycemia and lipid oxidation rate, lower carbohydrate oxidation, and lower serum vitamin C levels. CONCLUSIONS: Genotyping UCP2 and probably KCNJ11 may help to select the optimal antidiabetic therapy and improve disease prognosis, whereas the MTHFR gene may determine the need to monitor group B vitamin status and the risk of dyslipidemia.